2021
DOI: 10.1038/s41598-021-82079-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the histological features of the intestinal mucosa in malnourished adults of Bangladesh

Abstract: There is paucity of knowledge on the histological features of the intestinal mucosa in malnourished adults of Bangladesh. The purpose of the study was to explore the histological features of the intestinal mucosa in malnourished adults of Bangladesh and to compare the findings with their well-nourished counterparts. 64 adults (37 malnourished with body mass index, BMI < 18.5 kg/m2 and 27 controls with BMI > 18.5 kg/m2) from the Bangladesh Environmental Enteric Dysfunction (BEED) study, who underwent uppe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In mammals and birds, this cell line folds along its path through the GIT to increase its contact surface and thus its absorptive power, generating villi (raised portions) and invaginations between villi, which are termed crypts. In vivo models for studying gut physiology have shown hyperplastic crypts combined with reduced villus area, suggesting rapid tissue adaptation to nutrient shortages [ 30 , 31 , 32 ]. Heat stress may affect the intestinal structure by shortening villus height and increasing crypt depth, with a consequent decrease in the villus:crypt ratio, as shown in poultry [ 19 , 20 , 24 , 25 , 33 ], rodents [ 21 , 27 ], and pigs [ 22 , 23 ] ( Table 1 ).…”
Section: How Does Heat Stress Affect the Structure And Function Of The Intestinal Mucosa?mentioning
confidence: 99%
“…In mammals and birds, this cell line folds along its path through the GIT to increase its contact surface and thus its absorptive power, generating villi (raised portions) and invaginations between villi, which are termed crypts. In vivo models for studying gut physiology have shown hyperplastic crypts combined with reduced villus area, suggesting rapid tissue adaptation to nutrient shortages [ 30 , 31 , 32 ]. Heat stress may affect the intestinal structure by shortening villus height and increasing crypt depth, with a consequent decrease in the villus:crypt ratio, as shown in poultry [ 19 , 20 , 24 , 25 , 33 ], rodents [ 21 , 27 ], and pigs [ 22 , 23 ] ( Table 1 ).…”
Section: How Does Heat Stress Affect the Structure And Function Of The Intestinal Mucosa?mentioning
confidence: 99%
“…The gold standard for the diagnosis of EED involves a biopsy of the intestinal tissue and confirmation by histopathology. The Bangladesh Environmental Enteric Dysfunction (BEED) study revealed that 95% of adults residing in slums, who are asymptomatic, exhibit chronic non-specific intestinal inflammation, a hallmark feature of EED [ 20 ]. However, collecting endoscopy-guided small intestinal biopsy samples from clinically asymptomatic adults for routine diagnosis of EED is technically infeasible and, in some instances, unethical [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%